Aftershock Rate Changes at Different Ocean Tide Heights - Shebalin, P. N.; Baranov, A. A. (Frontiers in Earth Science, 2020)
The differential probability gain approach is used to estimate quantitatively the change in aftershock rate at various levels of ocean tides relative to the average rate model. An aftershock sequences are analyzed from two regions with high ocean tides, Kamchatka and New Zealand. The Omori-Utsu law is used to model the decay over time, hypothesizing an invariable spatial distribution. Ocean tide heights are considered rather than phases. A total of 16 sequences of M≥6 aftershocks off Kamchatka and 15 sequences of M≥6 aftershocks off New Zealand are examined. The heights of the ocean tides at various locations were modeled using FES 2004. Vertical stress changes due to ocean tides are here about 10-20 kPa, that is, at least several times greater than the effect due to earth tides. An increase in aftershock rate is observed by more than two times at high water after main M≥6 shocks in Kamchatka, with slightly less pronounced effect for the earthquakes of M=7.8, December, 15, 1971 and M=7.8, December 5, 1997. For those two earthquakes, the maximum of the DPG function is also observed at low water. For New Zealand, we also observed an increase in aftershock rate at high water after thrust type main shocks with M≥6. After normal-faulting main shocks there was the tendency of the rate increasing at low water. For the aftershocks of the strike-slip main shocks we observed a less evident impact of the ocean tides on their rate. This suggests two main mechanisms of the impact of ocean tides on seismicity rate, an increase in pore pressure at high water, or a decrease in normal stress at low water, both resulting in a decrease of the effective friction in the fault zone.